2019
DOI: 10.1186/s40168-019-0729-z
|View full text |Cite
|
Sign up to set email alerts
|

An expectation-maximization algorithm enables accurate ecological modeling using longitudinal microbiome sequencing data

Abstract: Background The dynamics of microbial communities is driven by a range of interactions from symbiosis to predator-prey relationships, the majority of which are poorly understood. With the increasing availability of high-throughput microbiome taxonomic profiling data, it is now conceivable to directly learn the ecological models that explicitly define microbial interactions and explain community dynamics. The applicability of these approaches is severely limited by the lack of accurate absolute cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 72 publications
0
46
0
Order By: Relevance
“…We anticipate that the incorporation of such environmental factors into future models would be an exciting avenue to study their influence on microbial community structure in vivo. Finally, hybrid methods that learn models from both longitudinal and cross-sectional data represent another promising direction to explore for studying general and individual specific microbiome dynamics (Li et al, 2019). Biomass estimates…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We anticipate that the incorporation of such environmental factors into future models would be an exciting avenue to study their influence on microbial community structure in vivo. Finally, hybrid methods that learn models from both longitudinal and cross-sectional data represent another promising direction to explore for studying general and individual specific microbiome dynamics (Li et al, 2019). Biomass estimates…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that an expectation maximization algorithm which couples gLVM parameter inference with scaling factor estimation (BEEM -originally designed for longitudinal data [Li et al, 2019]) can be transformed to work with cross-sectional data from communities that are at or near equilibrium (BEEM-Static). In benchmarking comparisons with simulated communities against 10 other methods that infer microbial interactions from cross-sectional data, we noted that while all other methods only improved slightly over random predictions (AUC-ROC<0.63), BEEM-Static exhibited high accuracy similar to estimation using true scaling values (AUC-ROC>0.88).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the fate of the communities in terms of composition was mainly driven by the availability of nutrients, which can be explained by a generic consumer-resource model. In addition, gLV models have been extensively applied to study the temporal evolution of communities [119] , [137] , [138] , [139] , [140] . These models enable predictions of community dynamics by taking into account growth rates and interactions strengths between microbes [141] .…”
Section: Community Approaches Of Metabolism Modellingmentioning
confidence: 99%
“…However, these methods implicitly ignore the constraint that relative abundances must sum to one and are therefore negatively correlated, making parameter estimates difficult to interpret. Li et al [34] suggest addressing this by inference of the latent overall biomass. Alternatively, Shenhav et al [21] suggested a linear mixed model with variance components, while representing the previous state microbial community using its quantiles instead of relative abundances.…”
Section: Introductionmentioning
confidence: 99%